(untitled) (Research, Society and Development, 2022)
The objective of this study was to evaluate the effect of adding a blend of organic acids, their salts, and lignin derivatives on the total bacterial count of the litter, as well as on its quality through measurements of pH, water activity, and moisture content. The research was conducted in three commercial poultry houses, with an area of 480m2 each, with the same housing date of the birds. Each poultry house received a different dosage, of 40, 80, and 120g/m², 48 hours before the accommodation of the birds, throughout the extension of the aviary. The collection of samples for analysis (microbiological, pH, water activity, and humidity) was performed in eight points in each house in different periods. A reduction in the total microbial count was observed six hours after the application of the blend in the three dosages evaluated (P<0.001). At 14 days of rearing, lower microbial counts were observed in the litter treated with 120g/m2 of the blend, indicating that this dosage can slow microbial growth throughout the rearing period (P<0.001). However, after 28 days, the addition of the blend in all dosages tested was not sufficient to slow microbial growth (P>0.05). The parameters pH, water activity, and moisture were not influenced by the additives applied on the bed (P>0.05). It is concluded that the acids and lignins added to the poultry litter, during the interval between flocks, have a mitigating effect on microbial proliferation until 14 days of housing.